The effect of the Rana Plaza disaster on shareholder wealth of retailers: Implications for sourcing strategies and supply chain governance⋆ - Jacobs, Brian W.; Singhal, Vinod R. (Journal of Operations Management, 2017)
AbstractSupply chain and reputational risks are often assumed to motivate firms to source production in developed, high‐cost countries rather than developing, low‐cost countries. To examine this assumption, we provide evidence from the collapse of the Rana Plaza building on April 24, 2013, which with its 1133 fatalities and 2438 injuries is seen as one of the worst industrial accidents in history. Do markets reactive negatively enough to such events to motivate firms to shift their sourcing strategy? We analyze the stock market reaction to the Rana Plaza disaster in the Bangladeshi ready‐made garment industry to address this question. Our analysis is based on a sample of 39 publicly traded global apparel retailers with significant garment sourcing in Bangladesh. Stock market reaction to retailers on the day of the Rana Plaza disaster is negative, but its magnitude and significance dissipate by the following day. We find no evidence of significant stock market reaction during the 11 trading days (approximately two weeks in calendar time) following the disaster. Retailers responded to the disaster by developing two different agreements to improve factory and worker safety in Bangladesh – the Accord on Fire and Building Safety in Bangladesh (AFBSB), and the Alliance for Bangladesh Worker Safety (ABWS). We find no evidence of significant stock market reaction to the announcements of the AFBSB and the ABWS. The insignificant negative economic impact from the Rana Plaza disaster suggests that retailers have little economic incentive to move sourcing out of Bangladesh or other low‐cost countries so as to reduce the risk of being involved in such events. We discuss the implications of our results for retailers, non‐governmental organizations (NGOs), garment factory owners in Bangladesh, the Bangladeshi government, and academic researchers.